Hypoglycemic Effect Pigeon Pea (Cajanus cajan) in Diabetes Mellitus - Suhaema Suhaema; I Gde Narda Widiada (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: Pigeon pea is a local food containing active substances and antioxidants that can potentially manage diabetes mellitus (DM). This disease has become a public health problem worldwide. As a result, various management efforts have been made, including utilizing potential foods in meal planning for people with diabetes.Objective: To determine the hypoglycemia effect of consuming pigeon pea (Cajanus cajan) in diabetes mellitus.Research Methods: This type of research is a literature review. Literature search used ProQuest, science direct, Pubmed, Garuda Garba, and Google Scholar databases. Strategies for finding articles using the PICOS framework, reviewing the quality of reports using the PRISMA checklist, and critical appraisal according to the experimental research design.Research Result. The eleventh study reviewed found a significant effect (p <0.05) on reducing blood sugar levels in animal and diabetes mellitus patients.Conclusion. The content of isoflavones and high antioxidant activity in pigeon pea (Cajanus cajan) can reduce blood glucose levels in mice, rats, and people with diabetes mellitus.